Earnings Quality as a Function of Capital Structure and Financial Signals : JEL Classification: M41 G32, G34, O16, L60 - Tanto, Tanto (Newinera Publisher, 2025)
In this regard the veracity of the corporate engagement in reporting earnings is of core interest in financial research especially in developing economies where regulation, disciplinary and governance infrastructure remains variable. This paper reconsiders the applicability of the four fundamental financial determinants, that is, the capital structure, earnings growth, firm size, and earnings persistence as a determinant of earnings quality in Indonesia in industrial sector. These variables are generally addressed in the available extents of literature as universally credible predictors; however, the institutions and the behavioural issues that define firms within a structurally fissured market place are rarely considerations, and few theories can be applied that are held to be reliably predictive. This study, using a regression model based on agency theory and signaling theory, and panel data collected on industrial firms which were listed in the Indonesia stock exchange during the period of 2019 and 2023; discovers that capital structure poses a rather influential influence positively on the earnings quality of firms. This is the result of creditor management encouraging reporting discipline in situations where internal governance is low. Conversely, earnings growth and firm size are not related closely with earnings quality, which means that the market is no longer using scale itself or expansion as a valid proxy of credibility. Even more urgently, the persistence of earnings is much more harmful on the scale, showing how too steady earnings could speak about manipulation instead of actual financial might.